Pengaruh Lama Perkecambahan Terhadap Rendemen, Kadar Antosianin, Vitamin E dan Aktivitas Antioksidan Kecambah Kedelai Hitam - Siti Asropah; Nurrahman Nurrahman; Wikanastri Hersoelistyorini (Jurnal Pangan dan Gizi, 2019)
Germination process can increase the nutritional value and functional properties that exist in the grain. Black soybeans contains anthocyanin, vitamin E and antioxidant activity that is beneficial to health. This study aims to determine the effect of long germination on rendement, anthocyanin, vitamin E levels and antioxidant activity on black soybean sprouts. Preliminary studies includes optimalization the length of germination and characterization of black soybean seeds. The main research includes physical and chemical analysis of rendement measurement, anthocyanin content, vitamin E content and antioxidant activity.  Then, analysis of proximate content on black soybean sprouts best result from long treatment of germination. The data measurement of black soybeans sprouts was obtained a digital scales and spectrophotometer UV-Vis. The results showed that (1) The germination has an effect on rendement, anthocyanin, vitamin E levels and antioxidant activity on black soybean sprouts. (2) In 40 hours long germination treatment showed anthocyanin level (91.84 mg / 10 g) and antioxidant activity (24.51% RSA) has the highest value. (3) The longer of germination has higher value on rendement percentage and vitamin E content.